Uji Aktivitas Antibakteri Ekstrak Rumput Laut Kappaphycus alvarezii terhadap Bakteri Vibrio parahaemolyticus, Vibrio campbellii, dan Aeromonas hydrophila - Ambartyasning, Errina Bening; Sasmita Julyantoro, Pande Gde; Widiastuti, Widiastuti (Journal of Marine Research and Technology, 2024)
The bacteria Vibrio parahaemolyticus and V. campbellii are the pathogens of Vibriosis in various marine cultured organisms. Moreover, Aeromonas hydrophila is the pathogen of the Motile Aeromonad Septicemia (MAS) disease. Therefore, it is needed to inhibit these bacteria's activity. Studies showed that the extract of seaweed Kappaphycus alvarezii could hinder the growth of gram-negative and gram-positive bacteria; however, the antibacterial activities against V. parahaemolyticus, V. campbellii, and Aeromonas hydrophila remain unknown. Thus, this study aimed to analyze the antibacterial activity, and the minimum inhibitory concentration of K. alvarezii extract against V. parahaemolyticus, V. campbellii, and A. hydrophila . K. alvarezii was collected from the cultured in the Geger Beach area, Badung Regency. The methanol K. alvarezii extracts with different concentrations (10, 5, 1, 0.05%) were dropped to the paper disk and placed on the bacterial tested cultures. Inhibition zone measurements were carried out every 6 hours during the 24-hour incubation period. Chloramphenicol and methanol were also tested as the positive and negative control, respectively. Results showed that the antibacterial activity was only demonstrated in 10% extract against V. campbellii with an inhibition zone of 12.5 mm .